Tipologi Home-based Enterprises di Sentra Industri Makanan Olahan Bandeng Kota Semarang Berdasarkan Tiga Modal Sustainable Livelihood - Izzah Khusna; Wido Prananing Tyas (Teknik PWK (Perencanaan Wilayah Kota), 2022)
The Center for Milkfish Processed Food Industry are scattered in several areas, three of which are located in Semarang Barat, Gayamsari, and Semarang Utara districts which has the largest milkfish production and investment value in Semarang City. Inside, there are Home-based Enterprises (HBE) for milkfish processing with various characteristics. There are 3 main points indicated that the existence of HBE for milkfish processing is a potential that can be developed, including SMEs, culinary tourism, and thematic villages. To develop that, it is necessary to identify the character of each HBE unit in the three districts. This study aims to identify the typology of HBE at the Center for Milkfish Processed Food Industry in Semarang City to identify the characters and prerequisites for the development of HBE types by using 3 sustainable livelihood asets as the determinant of research variables. The results showed that there were 3 types of HBE which formed by 51 units. Small HBEs is a group that tends to have lower capabilities in natural, human, and financial capital than other types. Middle profile HBEs is a group identified with abilities in a higher educational background and broader marketing. High profile HBEs is a group with higher capabilities in natural, human and financial capital than other types, so that it is possible to have a more stable and sustainable livelihood.